Strategic Utilization of Idle Government Assets in Malang City: An HBU AHP Approach for Sustainable Development - Allin Indraswary; Moh Khusaini; Bunga Hidayati (Journal of Governance, 2026)
Large portions of government-owned land in Malang City remain idle and underutilized, creating administrative, spatial, and ecological inefficiencies at a time when demand for sustainable urban space continues to rise. This study addresses the strategic gap in municipal asset governance by developing a structured decision-making framework to determine the optimal use of idle public land. Integrating the highest and best use framework with the analytical hierarchy process, expert judgments from key municipal agencies were analyzed to assess legal certainty, spatial feasibility, financial viability, and productivity potential. Findings reveal that legal certainty is the most influential criterion, underscoring persistent governance barriers in public asset management, while the preferred alternative is converting idle parcels into urban green open space. The study offers a scientifically grounded model that strengthens institutional decision-making and demonstrates how strategic optimization of idle government assets can advance sustainable development in medium-sized cities.